Rapid expansion and biodiversity impacts of the red devil cichlid (Amphilophus labiatus, Günther 1864) in Lake Sentani, Papua, Indonesia - HENDERITE L. OHEE; PUGUH SUJARTA; SURIANI BR. SURBAKTI; HOLLY BARCLAY (Society for Indonesian Biodiversity, 2018)
Ohee HL, Sujarta P, Br Surbakti S, Barclay H. 2018. Rapid expansion and biodiversity impacts of the red devil cichlid (Amphilophus labiatus, Günther 1864) in Lake Sentani, Papua, Indonesia. Biodiversitas 19: 2096-2103. The red devil cichlid (Amphilophus labiatus, Günther 1864) is one of ten exotic fish species inhabiting Lake Sentani. It is believed to be one of the most important threats to the native fish of Lake Sentani. This study aimed to document the distribution of red devil cichlids and the impacts of this species on native fish fauna. Fish were sampled in six locations in Lake Sentani using gill nets during February and March 2018. Fish species and abundance were recorded and used to calculate the relative abundance, dominance, species evenness, Shannon Wiener Index (H’) and the correlation between introduced and native fish species. A total of 836 fish belonging to 12 species were recorded across Lake Sentani. Mean fish diversity (H’=0.57) and evenness (E= 0.25) were low. The red devil cichlid is the most abundant fish recorded during our surveys (87.2% of total fish collected) and is now the most dominant fish in the lake (C=0.76). Moreover, it has colonized all areas sampled within the lake because of its ability to colonize new habitat and to successfully exploit a large diversity of trophic niches. However, Amphilophus labiatus was not found to be significantly correlated to native fish between different sites in Lake Sentani. The existence of endemic and native fish in Lake Sentani is now seriously threatened by the presence of the red devil cichlid throughout this lake.